(untitled) (Pesquisa Odontológica Brasileira, 2000)
The zinc oxide-eugenol cement is still widely used as a temporary restorative material. Its use is known, however, to disturb the curing process of composite resins used in the final restoration. Nevertheless, with the development of dentin bonding systems, total etch is used to remove or treat the smear layer before the construction of the composite resin restoration. The purpose of this study was to evaluate if the zinc oxide-eugenol cement influenced the microhardness of composite resin (Z100) restorations used in association with either one of two bonding systems (Scotchbond Multi-Purpose Plus® and Clearfil Liner Bond 2®). Forty molars were divided into four groups. For each bonding material there was a control group that did not receive cement and a group that received a temporary zinc oxide-eugenol restoration that was removed after seven days. The specimens were stored in a dry heat sterilizer at 37ºC, for seven days before the sectioning procedure. Microhardness was measured 0.3 mm far from the tooth-restoration interface by means of a SHIMADZU HMV 2000 apparatus, with a Knoop hardness tip of 50 g, for 45 seconds. Statistical analysis of the results was performed using ANOVA (alpha = 1%) and revealed no statistically significant differences in the microhardness of the composite resin, among the studied groups.